Effects of rpl1001 Gene Deletion on Cell Division of Fission Yeast and Its Molecular Mechanism - Wen Yu; Rongmei Yuan; Mengnan Liu; Ke Liu; Xiang Ding; Yiling Hou (Current Issues in Molecular Biology, 2024)
The rpl1001 gene encodes 60S ribosomal protein L10, which is involved in intracellular protein synthesis and cell growth. However, it is not yet known whether it is involved in the regulation of cell mitosis dynamics. This study focuses on the growth, spore production, cell morphology, the dynamics of microtubules, chromosomes, actin, myosin, and mitochondria of fission yeast (Schizosaccharomyces pombe) to investigate the impact of rpl1001 deletion on cell mitosis. RNA-Seq and bioinformatics analyses were also used to reveal key genes, such as hsp16, mfm1 and isp3, and proteasome pathways. The results showed that rpl1001 deletion resulted in slow cell growth, abnormal spore production, altered cell morphology, and abnormal microtubule number and length during interphase. The cell dynamics of the rpl1001Δ strain showed that the formation of a monopolar spindle leads to abnormal chromosome segregation with increased rate of spindle elongation in anaphase of mitosis, decreased total time of division, prolonged formation time of actin and myosin loops, and increased expression of mitochondrial proteins. Analysis of the RNA-Seq sequencing results showed that the proteasome pathway, up-regulation of isp3, and down-regulation of mfm1 and mfm2 in the rpl1001Δ strain were the main factors underpinning the increased number of spore production. Also, in the rpl1001Δ strain, down-regulation of dis1 caused the abnormal microtubule and chromosome dynamics, and down-regulation of hsp16 and pgk1 were the key genes affecting the delay of actin ring and myosin ring formation. This study reveals the effect and molecular mechanism of rpl1001 gene deletion on cell division, which provides the scientific basis for further clarifying the function of the Rpl1001 protein in cell division.